"I Can't Give Up When I Have Them to Care for": People's Experiences of Pets and Their Mental Health. (4th July 2021) - Hawkins, Roxanne D.; Hawkins, Emma L.; Tip, Liesbeth
ABSTRACT: Contact with animals has been increasingly recognized as being beneficial to mental health and wellbeing due to their therapeutic function, with "animal-assisted therapies" gaining in popularity. There is less research exploring how companion animals within the home impact upon mental health and wellbeing. This qualitative study explores people's experiences of the role of their pets in reducing or exacerbating their mental health symptomology and general wellbeing. One hundred and nineteen adults, 41 with a diagnosed mental health condition, and 70 recently struggling with their mental health, completed an online survey with open and closed questions to explore their experiences of their pets and mental health. Through thematic analysis, seven key themes were identified. Six themes encompassed benefits of pets; increased hedonic tone; increased motivation and behavioral activation; reduced anxiety symptoms and panic attacks; increased social connections and reduced loneliness; reduced risk behaviors; and coping and aiding the recovery process. One theme encompassed negative impacts: increased negative feelings and emotional strain. Notably, pets reduced urges of self-harm, and prevented onsets of panic attacks and suicide attempts. Both direct mechanisms (e.g., lowering physiological anxiety through physical touch) and indirect mechanisms (e.g., elevating mood through humor, increased mindfulness and disrupting rumination) were identified. These findings encapsulate the complex roles that pets can play in people's mental health and wellbeing, and highlights that even when the human–pet relationship is regarded positively, pets cannot "treat" mental health difficulties, and should not be viewed as such. Mental health practitioners should be aware and considerate of the importance of pets in people's lives as well as individual differences in the potential capability of pets to both reduce or exacerbate mental health symptomology and overall wellbeing.